Extremes of weight gain and weight loss with detailed assessments of energy balance: Illustrative case studies and clinical recommendations. Issue 3 (June 2014) - Falck, Ryan S.; Shook, Robin P.; Hand, Gregory A.; Lavie, Carl J.; Blair, Steven N.
Abstract: Extreme weight changes, or changes in weight greater than 10 kg within a 2-year period, can be caused by numerous factors that are much different than typical weight fluctuations. This paper uses two interesting cases of extreme weight change (a female who experienced extreme weight gain and a male who experienced extreme weight loss) from participants in the Energy Balance Study to illustrate the physiological and psychosocial variables associated with the weight change over a 15-month period, including rigorous assessments of energy intake, physical activity (PA) and energy expenditure, and body composition. In addition, we provide a brief review of the literature regarding the relationship between energy balance (EB) and weight change, as well as insight into proper weight management strategies. The case studies presented here are then placed in the context of the literature regarding EB and weight change. This report further supports previous research on the importance of regular doses of PA for weight maintenance, and that even higher volumes of PA are necessary for weight loss. Practitioners should emphasize the importance of PA to their patients and take steps to monitor their patients' involvement in PA.